Electroactive LbL films of metallic phthalocyanines and poly(O-methoxyaniline) for sensing - Santos, Amanda C.; Zucolotto, Valtencir; Constantino, Carlos J. L. [UNESP]; Cunha, Helder N.; dos Santos, Jos R.; Eiras, Carla (Springer, 2007)
Multilayered nanostructured films have been widely investigated for electrochemical applications as modified electrodes, including the layer-by-layer (LbL) films where properties such as thickness and film architecture can be controlled at the molecular level. In this study, we investigate the electrochemical features of LbL films of poly (o-methoxyaniline; POMA) and tetrasulfonated phthalocyanines containing nickel (NiTsPc) or copper (CuTsPc). The films displayed well-defined electroactivity, with redox pairs at 156 and 347 mV vs SCE, characteristic of POMA, which allowed their use as modified electrodes for detecting dopamine and ascorbic acid at concentrations as low as 10(-5) M.
Keywords: LbL films; dopamine; ascorbic acid; sensors; phthalocyanines